Development of Mesoporous Materials from Biomass Ash with Future Applications as Adsorbent Materials - Pizarro-Konczak, J; Castillo-Castillo, X; Gómez-Barrena, M; Diaz-Navarro, C (Elsevier B.V., 2020)
This paper proposes the synthesis and functionalization of a low-cost mesoporous material from biomass ashes with the aim of obtaining a new adsorbent material, thereby recycling and transforming an environmental liability into a material with added value. Biomass ashes are an environmental liability, composed mainly of aluminosilicates, which have been modified with the help of a surfactant (Pluronic P-123) to model and modify its porous structure. The functionalization of the synthesized material was carried out with N, N-dimethylacetamide (DMAC) and glycine (GLY) in order to improve the adsorption capacity of the synthesized material. The materials obtained in this article were characterized by adsorption-desorption isotherms of N2 at 77 K, X-ray fluorescence (XFR), elemental analysis (EA), X-Ray diffraction (XRD), Fourier-transform infrared spectrometry (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoemission spectroscopy (XPS). The adsorption capacity of the synthesized matrices has been tested in batch and electrochemical systems. The surface areas obtained by the BET method were 18.49 m2 g−1 for pure ashes (CBT) and 22.84 m2 g−1 for modified ashes, and the adsorption capacities of Fe3+ ions were of about 80.49% for bare SC1, 83.27% for SC1-GLY and 95.41% for SC1-DMAC. © 2020 Elsevier Inc.